Factors affecting overall care experience for people living with rare conditions in the UK: exploratory analysis of a quantitative patient experience survey - Jennifer Jones; Marie Cruddas; Amy Simpson; Nick Meade; Daphnee Pushparajah; Michelle Peter; Amy Hunter (Orphanet Journal of Rare Diseases, 2024)
Abstract Background Although individually rare, collectively, rare conditions are common and affect a large number of people and are often chronic, life threatening and affect multiple body systems; the majority of them have no effective treatment. The literature has identified many specific challenges for those living with rare conditions, however, we do not know which of these in combination are most likely to impact how someone rates their overall experience of care. The aim of this study is to do further exploratory analysis of the Genetic Alliance UK 2020 Rare Experience survey data to identify which variables are most strongly associated with respondents’ overall care experience. Results There were strong associations between most of the selected survey variables and the overall rated experience of care variable. In the multiple linear regression only nine variables remained in the best fit model: ‘Trust and confidence in hospital staff involved in ongoing care’; ‘Satisfaction with information provided by healthcare professionals—following diagnosis’; ‘The professionals providing care work as a team’; ‘Feel care is coordinated effectively’; ‘The timing and frequency of appointments are convenient for the patient/carer/family’; ‘Whether or not there is a specific healthcare professional to ask questions of about the rare/undiagnosed condition’; ‘Experience of searching for a diagnosis’; ‘Knowledge of whether there is a specialist centre for the condition’; and ‘Number of different clinics attend for the condition’. Conclusions Our findings indicate the challenges that play the largest part in explaining the varied experiences with rare disease healthcare in the UK for our survey respondents. These challenges should be further investigated with a broader sample of people affected by rare conditions, ideally through the implementation of a comprehensive national rare condition patient registry. Our findings highlight an important potential gap in the Framework, ‘trust and confidence in healthcare professionals’; further research is required to fully understand the foundations of trust and confidence.